Mental Health and Recreational Angling in UK Adult Males: A Cross-Sectional Study - Jason J. Wilson; Mike Trott; Mark A. Tully; Rosie K. Lindsay; Matt Fossey; Lauren Godier-McBard; Laurie T. Butler; Andy Torrance; Lee Smith (MDPI AG, 2023)
Exposure to aquatic environments (i.e., blue spaces) can lead to improved mental health and well-being. One meaningful way to spend time in blue spaces is through recreational angling, although limited scientific literature exists on this topic. The present study aims to examine the relationship between recreational angling and mental health and well-being in a sample of UK adult male anglers. A cross-sectional online survey asked questions about demographic characteristics, participation in recreational angling, physical activity levels, diagnosis of psychiatric disorders, and mental health and well-being. Relationships between angling status (i.e., how often and how long participants angled for) and mental health variables were determined using regression models adjusted for age. In total, 1752 participants completed the survey. The regression models found that those who took part in angling more regularly had reduced odds of having depression (p < 0.001), schizophrenia (p = 0.001), suicidal thoughts (p < 0.001), and deliberately self-harming (p = 0.012), in addition to having a higher mental well-being and lower symptoms of depression and anxiety compared to those taking part in angling less frequently. In general, the findings suggest that encouraging frequent participation in recreational angling could be a dual method strategy for promoting relaxation and positive mental health, as well as encouraging increased levels of physical activity in those with mental health issues.